2003
DOI: 10.2337/diabetes.52.2.380
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of GLP-1 on Glucose-Stimulated Insulin Secretion

Abstract: The intestinally derived hormone glucagon-like peptide 1 (GLP-1) (7-36 amide) has potent effects on glucosemediated insulin secretion, insulin gene expression, and ␤-cell growth and differentiation. It is, therefore, considered a potential therapeutic agent for the treatment of type 2 diabetes. However, the dose-response relationship between GLP-1 and basal and glucose-stimulated prehepatic insulin secretion rate (ISR) is currently not known. Seven patients with type 2 diabetes and seven matched nondiabetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
341
1
14

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(385 citation statements)
references
References 36 publications
29
341
1
14
Order By: Relevance
“…In other words, with GLP-1 the subjects showed a completely normal insulin response to glucose. A similar observation (that GLP-1 can restore beta-cell responsiveness glucose in patients with Type 2 diabetes) was made by a study using an entirely different approach [79]. Moreover, the normal glucoseinduced inhibition of glucagon secretion was completely restored.…”
Section: Incretin Function In Diabetessupporting
confidence: 65%
See 1 more Smart Citation
“…In other words, with GLP-1 the subjects showed a completely normal insulin response to glucose. A similar observation (that GLP-1 can restore beta-cell responsiveness glucose in patients with Type 2 diabetes) was made by a study using an entirely different approach [79]. Moreover, the normal glucoseinduced inhibition of glucagon secretion was completely restored.…”
Section: Incretin Function In Diabetessupporting
confidence: 65%
“…Indeed, in 1993 one study could show that an iv infusion of GLP-1 could completely normalise plasma glucose concentrations, even in patients with advanced Type 2 diabetes [83]. As mentioned above, addition of GLP-1 might restore glucose-induced insulin secretion to normal values in the patients [77,79]. However, it should be noted that GLP-1 not only potentiates glucose induced insulin secretion, but also has numerous other effects, all of which seem to be desirable in the context of treating Type 2 diabetic patients (Table 1).…”
Section: Incretin Hormones As Therapeutic Agentsmentioning
confidence: 99%
“…10,11 Clinical studies have shown that diabetic individuals can exhibit decreased GLP-1 secretion, yet physiological responses to this incretin hormone remain largely intact. [12][13][14][15] As a result, therapeutic efficacy of GLP-1-receptor agonists has been demonstrated in individuals with type-2 diabetes. Beneficial effects of GLP-1 in the treatment of type-1 diabetes have also been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now accepted that there is no specific molecular defect of the GIP receptor in established diabetes, first-degree relatives or gestational diabetes [15][16][17]. Recognition that GLP-1 action is also impaired, to a lesser extent than GIP action, in type 2 diabetes [18], suggests that the diminished insulin response is linked to generalised beta cell secretory dysfunction, presumably stemming from beta cell glucose insensitivity [19].…”
Section: Introductionmentioning
confidence: 99%